Stage of visual field loss and age at diagnosis in 1988 patients with different glaucomas: implications for glaucoma screening and driving ability - Gramer, Gwendolyn; Gramer, Eugen (International ophthalmology, 2018)
PurposeTo compare stage of visual field loss (VFL) and age at diagnosis between patients with different types of glaucoma with regard to glaucoma screening and driving ability.MethodsIn a cross-sectional study of 1988 consecutive patients with different types of glaucoma VFL at diagnosis and age at diagnosis were assessed. Patients with binocular advanced or severe VFL were classified unable, patients with no VFL in one eye and VFL I-V (Aulhorn classification) in the other eye able, all other constellations questionably able to drive.ResultsThere were significant differences in age at diagnosis between different glaucomas and between patients with different stages of VFL at diagnosis. Age-related assessment of VFL at diagnosis in normal tension glaucoma (NTG) compared to primary open-angle glaucoma (POAG) showed that NTG is not a disease of the elderly but a disease with late diagnosis at severe VFL. In POAG a solely age-related glaucoma screening, e.g. from the age of 50 years, does not sufficiently lead to diagnosis at an early stage of the disease. In POAG solely based on binocular VFL 11.5% of patients were judged unable, 29.2% questionably able to drive, in NTG 19.6%/43.1%, pigmentary glaucoma 16%/22%, pseudoexfoliation glaucoma 9.1%/16.7%, and in primary angle-closure glaucoma 14.6%/30%.ConclusionsDepending on type of glaucoma more than 50% of patients require counselling regarding safe driving as part of clinical care. A disease-specific, age-related perimetric examination considering additional risk factors like family history of glaucoma is essential for early detection of glaucoma and road safety.